The Graeco-Bactrian and Indo-Greek World - Mairs, Rachel (Routledge Worlds Ser, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- List of Tables -- List of Contributors -- Chapter 1 Introduction -- Preliminary remarks -- Hellenistic Central Asia: A brief introduction -- Outline -- Acknowledgements -- References -- Part I Interactions -- Chapter 2 The Seleukid Empire -- Introduction -- The conquests of Seleukos I Nikator (311-281 BCE) -- Apama, Demodamas, and Antiochos -- The making of Seleukid Central Asia (294-261 BCE) -- Seleukid sites in Central Asia -- From Antiochos I to Antiochos III (261-222 BCE) -- The reign of Antiochos III the Great (222/1-187 BCE) -- Conclusion: The impact of empire -- Notes -- References -- Chapter 3 South Asia -- Introduction -- The Mauryan dynasty in Graeco-Roman and South Asian literature -- Aśokan inscriptions and Buddhist sources -- Mauryan sites and artefacts -- Archaeology -- Aśokan pillars -- Stone sculpture -- Punch-marked coins -- Conclusions -- References -- Chapter 4 Parthia -- Introduction -- Geography -- History of research -- The Achaemenid period -- The Hellenistic and Parthian periods -- Notes -- References -- Chapter 5 Central Asia and the Steppe -- A brief cultural geography of the northern frontier -- Sources and methodological problems -- Elite networks across Central Asia during the pre-Achaemenid and Achaemenid period -- The coming of the Greeks: consequences for Central Asia -- The independence of Sogdiana -- The formation of the Xiongnu Steppe Empire and its consequences across Central Asia -- Age of migrations? New networks and new sources on the post-Hellenistic period -- 'Hellenism' as an element in the Central Eurasian prestige economy at the turn of the millennium -- Notes -- References -- Chapter 6 China and Bactria during the reign of Emperor Wu in written tradition and in archaeology.